2019
DOI: 10.1111/1440-1681.13191
|View full text |Cite
|
Sign up to set email alerts
|

Morphine stimulates angiogenesis through Akt/mTOR/eIF4E activation under serum deprivation or H2O2‐induced oxidative stress condition

Abstract: Morphine is an opioid analgesic drug routinely used to treat pain in several medical conditions including cancer. Increasing evidence has shown that morphine can directly modulate cancer growth via regulating angiogenesis. In this work, we investigated the effect of morphine on angiogenesis under pathological conditions. We showed that morphine, in a concentration typical of that observed in patient's blood, stimulates tumour angiogenesis under serum deprivation and H2O2‐induced oxidative stress conditions. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The reason behind this discrepancy is unclear, but it may be a result of differences in model systems, endothelial type, drug concentrations and experimental conditions. In support of this possibility, our finding is consistent with the recent study by Zhang et al that morphine stimulates angiogenesis after serum deprivation [ 9 ] because our experimental settings are similar to Zhang et al’s work. We next showed that oxycodone at the same concentration range also displayed pro-angiogenic activity, but was less potent than morphine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reason behind this discrepancy is unclear, but it may be a result of differences in model systems, endothelial type, drug concentrations and experimental conditions. In support of this possibility, our finding is consistent with the recent study by Zhang et al that morphine stimulates angiogenesis after serum deprivation [ 9 ] because our experimental settings are similar to Zhang et al’s work. We next showed that oxycodone at the same concentration range also displayed pro-angiogenic activity, but was less potent than morphine.…”
Section: Discussionsupporting
confidence: 93%
“…Morphine, fentanyl, oxycodone and codeine are μ-opioid receptor agonists but can bind to and activate δ and κ with differential affinity [ 8 ]. Among these four commonly used opioids, morphine has been mostly studied under preclinical settings for its direct effect on tumor cell and angiogenesis but the conclusions are contradictory [ 9 12 ]. Morphine stimulates angiogenesis under serum deprivation and oxidative stress conditions [ 9 ] whereas also suppresses angiogenesis associated with tumor growth in mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diminution in mTOR phosphorylation in the DG after the expression of CPA was due to the recall of aversive memories associated with morphine withdrawal and not to opiates exposure given that, when other group of morphine-treated rats were tested for CPA extinction, mTOR phosphorylation in their DG was similar to that of controls. Moreover, several studies have reported an activation (phosphorylation) of mTOR induced by opiates that mediates some of their effects, such as tolerance, hyperalgesia and angiogenesis, among others [40][41][42][43][44]. mTOR activity, through protein synthesis and actin dynamics mediated by mTORC1 and mTORC2, respectively, has been related as well with distinct aspects of learning and memory, such as late long-term potentiation (L-LTP) that underlies LTM [39].…”
Section: Discussionmentioning
confidence: 99%